Make a Silence: Musical Dialogues in Asia - Norton, Barley (Journal of Anthropological Films, 2020)
The Hanoi New Music Festival 2018 was an historic event. It was the largest festival of exploratory forms of new music that has ever been held in Vietnam, and artists from countries across Southeast Asia and Japan came to Hanoi to participate. The film Make a Silence - Musical Dialogues in Asia showcases the diverse, multimedia performances that took place at the Festival, including sound art for theatre and video, underground music and free improvisation. Like the Festival itself, Make a Silence is a sensory feast of musical and visual exploration. Combining vivid artistic images, conversations with musicians and footage of concerts, the film meditates on transnational dialogue in the contemporary music scene in Asia. Artists featured in the film include Otomo Yoshihide (Japan), Trần Thị Kim Ngọc (Vietnam), Jiradej Setabundhu (Thailand), Red Slumber (Vietnam), Siew-Wai Kok (Malaysia), Otto Sidharta (Indonesia) and Yii Kah Hoe (Malaysia). The film is based on long-term ethnographic research in Vietnam by the director. It examines how transnational circuits of musical exchange in the new music scenes in Asia intersect with postcolonial politics, thereby challenging the often-presumed hegemony of Euro-American lineages of contemporary music.